(untitled) (LEARNing Landscapes, 2021)
The maintenance of heritage language is essential to immigrant children’s linguistic, cultural, and social development. While there is a large body of literature on heritage language, how heritage language is practiced at home remains largely unknown. Engaging in an autobiographical narrative inquiry, I tell and retell stories of our pedagogical practices in the home context. I seek to bridge the research gap with new understandings of the “parent knowledge” that immigrant parents bring to bear in heritage language education. I invite you into my home and immigrant family’s language journey to witness the efforts, challenges, and rewards of learning heritage language.